The quality of the work environment on achieving the organization excellence Case of Sudanese Thermal Power Generating Company - Mhmuod, Nagwa Abdallah (Journal of Economic, Administrative and Legal Sciences, 2020)
The objective of the study is to understand the impact of the quality of the work environment represented in the physical work environment, job stability, and career planning in the organizational excellence of the company. The study used a descriptive-analytical approach for the analysis, where a questionnaire was composed of 31 paragraphs distributed to a number of 330 employees of the Sudanese Thermal Power Generating Company. The results showed that there is no interest in the physical work environment. Further, the process of Career Planning and Development in the company is characterized by a lack of transparency. Furthermore, the lack of security and stability of all employees of the company. The results also showed a statistically significant relationship between the quality of the work environment and the organizational excellence of the company. The study recommended the importance of providing a suitable work environment for all employees and customers of the company, the company should adopt a clear policy for career planning based on assessing the level of job performance and according to the performance measures of each job, working to create a culture of motivation and supportive of excellence of the company based on knowledge sharing and exchange of experiences, and adoption of a specific model of institutional excellence as an entrance to the development of individual and institutional performance to achieve a strategic vision of the company.